PEMBINAAN DAN PENGAWASAN CAMAT TERHADAP ALOKASI DANA DESA DI DESA GEMA KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR TAHUN 2012-2014 - Solehan "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Head has the authority to direct and oversee the management of the Village Fund Allocation, coaching and supervision will be made by the Head of Kampar Kiri Hulu is only socialize Head to Head Village about making the preparation of the budget cap Village Fund Allocation. This study aims to determine the guidance and supervision of the Head of the Village in the Village Fund Allocation Gema Kampar Kiri Hulu District of Kampar. This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. Guidance and supervision of Kampar Kiri Hulu subdistrict leader in the management of the Village Fund Allocation in the village of Gema in 2012-2014 seen from the financial management of the village is already well underway with providing guidance and consultation in the preparation of Administrative APBDes and orderly village finances. While the ADD management supervision has not been going up where there are execution of the work comes from the ADD results of his work is not as expected. In the implementation of the guidance and supervision of the management of ADD in the village Gema there are obstacles in the form of the unavailability of technical personnel, ADD is more widely used for routine expenditure rather than capital expenditure, supervision of BPD in the implementation of APBDes not run well. Keywords: Guidance, Control, Village Fund Allocation